Kinetic Studies on the Selective Oxidation of Benzyl Alcohols in Organic Medium under Phase Transfer Catalysis - K. Bijudas; P. Bashpa; T. D. Radhakrishnan Nair (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
Kinetic studies on the oxidation of benzyl alcohol and substituted benzyl alcohols in benzene as the reaction medium have been studied by using potassium dichromate under phase transfer catalysis (PTC). The phase transfer catalysts (PT catalysts) used were tetrabutylammonium bromide (TBAB) and tetrabutylphosphonium bromide (TBPB). Benzyl alcohols were selectively oxidised to corresponding benzaldehydes in good yield (above 90%). The order of reactivity among the studied benzyl alcohols is p - OCH3 > p - CH3 > - H > p - Cl. Plots of log k2 versus Hammett's substituent constant (s) has been found to be curve shaped and this suggests that there should be a continuous change in transition state with changes in substituent present in the substrate from electron donating to electron withdrawing. A suitable mechanism has been suggested in which the rate determining step involves both C - H bond cleavage and C - O bond formations in concerted manner. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)